Multiwavelength micropulse lidar for atmospheric aerosol investigation - Posyniak, Michał; Stacewicz, Tadeusz; Miernecki, Maciej; Jagodnicka, Anna K.; Malinowski, Szymon P. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
Multiwavelength micropulse lidar (MML) designed for continuous atmospheric sounding is presented. In its optical emitter, a diode pumped pulsed Nd:YAG laser is used. The laser generates three wavelengths: 1064, 532 and 355 nm. Energies of light pulses are about 30, 15 and 7 μJ, respectively, while their repetition rate is 2 kHz. Returning light is collected by a Cassegrain telescope with the mirror of 170 mm in diameter. Then, the signal is spectrally separated by a polichromator built with dielectric interference and colour filters. Detection of the signals is performed with three photomultipliers and a multiscaling photon counter. Preliminary results of investigation of aerosol properties during COAST 2009 experiment on the Baltic Sea are presented.
Optica Applicata, Vol. 40, 2010, nr 3, s. 623-632
Keywords: optyka; micropulse lidar; atmospheric aerosol; optical teledetection